Analysis of the Influence of Compensation, Organizational Culture, and Leadership on Job Satisfaction and Their Impact on Employee Performance at PT. Perkebunan Nusantara II Kebun Bandar Klippa - Tamado Simon Sagala; Rasmulia Sembiring; Siti Normi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to find out how much influence compensation, organizational culture, and leadership have on employee performance at PT. Nusantara Pekebunan II Bandar Klippa Garden, both partially and simultaneously, and how Work Satisfaction mediates it. The research method used was descriptive-quantitative. Research results Indirectly, compensation, organizational culture, and leadership's influence on performance can be mediated by job satisfaction. where the direct effect of compensation on employee performance is 0.261 while the indirect effect is 0.078, so it can be concluded that the direct effect of compensation on employee performance is higher than the indirect effect. The direct effect of organizational culture is 0.059 on employee performance, while the indirect effect is 0.021, so it can be concluded that the direct effect of organizational culture on employee performance is higher than the indirect effect. The direct effect of leadership is 0.355 on employee performance, while the indirect effect is 0.128, so it can be concluded that the direct effect of leadership on employee performance is higher than the indirect effect.